The Impact of Financial Ratios on Financial Performance of Saudi Food Production Companies - Alqudah , Mustafa Abdullah; Alrowais , Sattam Saud (Finance and Business Economies Review, 2023)
This study aimed to identify the impact of financial ratios on the financial performance of Saudi food production companies, measured by return on sales for the period 2019 - 2022. The statistical program E-VIEWS was used, the study sample consisted of all Saudi food production companies which was (15) companies listed on Saudi Exchange Market (Tadawul). The results of the study indicated that there was significantly and positively relationship between company’s financial performance from one side and company’s debt ratios, company’s current ratio, company’s productivity, and customer’s satisfaction from the other side, the study also found negative relationship between the company's financial performance and company’s size.